2019
DOI: 10.1111/ele.13245
|View full text |Cite
|
Sign up to set email alerts
|

When do herbivorous insects compete? A phylogenetic meta‐analysis

Abstract: When herbivorous insects interact, they can increase or decrease each other's fitness. As it stands, we know little of what causes this variation. Classic competition theory predicts that competition will increase with niche overlap and population density. And classic hypotheses of herbivorous insect diversification predict that diet specialists will be superior competitors to generalists. Here, we test these predictions using phylogenetic meta‐analysis. We estimate the effects of diet breadth, population dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 51 publications
1
42
1
Order By: Relevance
“…At first glance, one may not expect competition to influence internal feeders any differently than other sorts of herbivorous arthropods, but endophytic species, which are somewhat sessile, may be expected to compete even more strongly for their restricted resource than ectophytic species, which can often move to other food sources if they encounter competition (Denno et al, 1995). And a recent study found this to be the case; in particular, endophytic species appear to compete strongly with sap feeders (Bird et al, 2019). Therefore, once a lineage evolved an ability to be surrounded by plant tissue (e.g., boring, galling, mining, etc.…”
Section: Competitionmentioning
confidence: 99%
See 3 more Smart Citations
“…At first glance, one may not expect competition to influence internal feeders any differently than other sorts of herbivorous arthropods, but endophytic species, which are somewhat sessile, may be expected to compete even more strongly for their restricted resource than ectophytic species, which can often move to other food sources if they encounter competition (Denno et al, 1995). And a recent study found this to be the case; in particular, endophytic species appear to compete strongly with sap feeders (Bird et al, 2019). Therefore, once a lineage evolved an ability to be surrounded by plant tissue (e.g., boring, galling, mining, etc.…”
Section: Competitionmentioning
confidence: 99%
“…), competition with some ectophytic species may have given endophytic species an advantage that may have first allowed the lineage to succeed and then to diversify. Indeed, competition among endophytic species appears to be quite common ( Denno et al, 1995 ), suggesting that selection pressures may force endophytic species to partition resources to minimize competition ( Bird et al, 2019 ). There is evidence of competition between free-living folivores and internal feeders ( Denno et al, 1995 ; Kaplan and Denno, 2007 ; Bird et al, 2019 ), perhaps providing a glimpse of competitive interactions that may have encouraged endophagy, but such conclusions would be premature.…”
Section: Selection Pressures Leading To Evolution Of Endophytic Feedimentioning
confidence: 99%
See 2 more Smart Citations
“…It could be that major evolutionary changes in host use are caused by major declines in fitness on ancestral hosts. Such declines could be due to a variety of factors including increased competition for diminished host‐plant resources, the evolution of novel host defenses, the invasion of host herbivore assemblages by new species, and changes in natural enemy communities (Bird, Kaczvinsky, Wilson, & Hardy, ; Kenis et al, ; Segraves & Anneberg, ). Regardless of the cause, if major evolutionary changes in herbivore diet are sparked by such calamities, we might expect such changes to be linked to long‐term decreases in herbivorous insect species diversity.…”
Section: Discussionmentioning
confidence: 99%